Experimental and numerical studies of a strip footing on geosynthetic-reinforced sand. Issue 5 (25th September 2020) - Xu, Youwei; Yan, Guanxi; Williams, David J.; Serati, Mehdi; Scheuermann, Alexander; Vangsness, Timothy
Abstract : The behaviour of footings on geosynthetic-reinforced soils has been investigated by many researchers through experimental and numerical modelling under stress-controlled or strain-controlled conditions. A new experimental set-up was designed under a stress-controlled condition, with the application of the particle image velocimetry (PIV) technique. A series of model footing tests was carried out using this equipment to investigate the behaviour of the geosynthetic-reinforced soil below a strip footing. The deformation inside the soil mass below the strip footing was determined using the PIV technique. The reinforcing performances of single-layer and multi-layer geotextile and single-layer geogrid embedded at different depths were compared and discussed by analysing the load–settlement curves. It is found that there is a stepwise increase phenomenon in settlement under the stress-controlled condition. The ultimate bearing capacities were determined from the obtained stepwise load–settlement curves using three approaches: the tangent intersection method, the tail linear method and the allowable settlement method. The three approaches were coded in a Python program in order easily to determine and compare the results. In addition, the experimental model footing tests were simulated using the finite-element method under the same stress condition with good agreement for a settlement range within 0·1 B .